(untitled) (Bangladesh Journal of Medical Education, 2017)
This paper aims to address ethical issues related to the assisted reproductive technology of artificial insemination [AI] from the Western ethical perspective. Our evaluation suggests that Western ethicists offer some arguments both for and against the application of this modern assisted reproductive technology. Bangladesh Journal of Medical Education Vol.5(1) 2014: 10-14